2012
DOI: 10.1530/rep-11-0464
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Sertoli cell proliferation: defining the response interval to an inhibitor of estrogen synthesis in the boar

Abstract: Sertoli cell proliferation occurs in two major waves after birth, one neonatally and another prepubertally, each contributing to final testicular size and sperm production. However, little is known about the regulation of either wave. We have previously shown that letrozole, an inhibitor of estrogen synthesis, increases Sertoli cell number and testicular size at sexual maturity in boars. These studies were conducted to determine whether letrozole affects the first or second proliferative wave. Boars were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Five littermate pairs were evaluated at each age except four littermate pairs were evaluated at the 8 week timepoint. E 2 levels were dramatically reduced as previously reported for these animals but testosterone, follicle-stimulating hormone, luteinizing hormone, inhibin and prolactin were not affected by letrozole treatment (At-Taras et al 2006, Berger et al 2012, Berger & Conley 2014a. To block the effects of endogenous estrogen mediated by ESR1 and ESR2, one boar in littermate trios of boars (total of five litters) received at least 125 mg fulvestrant, a nuclear estrogen receptor (ESR1 and ESR2) antagonist and G protein-coupled estrogen receptor (GPER) agonist (Tocris USA, Ellisville, MO, USA)/kg body weight per day via Alzet osmotic pumps (models 2ML4 and 2ML2; Durect Corporation, Cupertino, CA, USA) as described previously (Berger et al 2013).…”
Section: Experimental Designsupporting
confidence: 76%
“…Five littermate pairs were evaluated at each age except four littermate pairs were evaluated at the 8 week timepoint. E 2 levels were dramatically reduced as previously reported for these animals but testosterone, follicle-stimulating hormone, luteinizing hormone, inhibin and prolactin were not affected by letrozole treatment (At-Taras et al 2006, Berger et al 2012, Berger & Conley 2014a. To block the effects of endogenous estrogen mediated by ESR1 and ESR2, one boar in littermate trios of boars (total of five litters) received at least 125 mg fulvestrant, a nuclear estrogen receptor (ESR1 and ESR2) antagonist and G protein-coupled estrogen receptor (GPER) agonist (Tocris USA, Ellisville, MO, USA)/kg body weight per day via Alzet osmotic pumps (models 2ML4 and 2ML2; Durect Corporation, Cupertino, CA, USA) as described previously (Berger et al 2013).…”
Section: Experimental Designsupporting
confidence: 76%
“…Our previous and present studies showed that 17beta-estradiol promoted immature boar Sertoli cell proliferation (Wang et al 2010).However, some studies in vivo indicated that estrogen regulated immature boar Sertoli cell proliferation negatively (Ramesh et al 2007;Berger et al 2012). Reduced levels of estradiol in boar testicular tissue increased Sertoli cell number, but the level of testicular estradiol could still be detected (Ramesh et al 2007).…”
Section: Discussionmentioning
confidence: 46%
“…Some studies also showed that estrogen increased Sertoli cell number in the hypo-gonadal (hpg) mouse, as well as cultured immature rat or boar Sertoli cells (Wang et al 2010;Lucas et al 2008;Baines et al 2008). However, other studies found that letrozole, an inhibitor of estrogen synthesis, increased proliferation of boar Sertoli cells during the first wave (Ramesh et al 2007;Berger et al 2012). This suggests that estrogen likely plays an important role in the process of immature Sertoli cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Animal treatment from 11 to 16 weeks of age, testicular aromatase levels and testicular estradiol levels for these animals was previously described (Berger et al. ). A second group of animals (5 litters) were treated with the aromatase inhibitor from 1 to 6 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…One member of each littermate pair was treated with 0.1 mg letrozole/ kg body weight and the other member received the vehicle; this treatment effectively inhibits aromatase and reduces circulating oestrogens, and preliminary trials indicated that 1.0 mg letrozole/kg body weight did not further reduce circulating oestrogens (At-Taras et al 2006). Animal treatment from 11 to 16 weeks of age, testicular aromatase levels and testicular estradiol levels for these animals was previously described (Berger et al 2012). A second group of animals (5 litters) were treated with the aromatase inhibitor from 1 to 6 weeks of age.…”
Section: Animals and Samplingmentioning
confidence: 99%